Dark Pathways to Achievement in Science: Researchers' Achievement Goals Predict Engagement in Questionable Research Practices. Issue 6 (August 2019) - Janke, Stefan; Daumiller, Martin; Rudert, Selma Carolin
Questionable research practices (QRPs) are a strongly debated topic in the scientific community. Hypotheses about the relationship between individual differences and QRPs are plentiful but have rarely been empirically tested. Here, we investigate whether researchers' personal motivation (expressed by achievement goals) is associated with self-reported engagement in QRPs within a sample of 217 psychology researchers. Appearance approach goals (striving for skill demonstration) positively predicted engagement in QRPs, while learning approach goals (striving for skill development) were a negative predictor. These effects remained stable when also considering Machiavellianism, narcissism, and psychopathy in a latent multiple regression model. Additional moderation analyses revealed that the more researchers favored publishing over scientific rigor, the stronger the association between appearance approach goals and engagement in QRPs. The findings deliver first insights into the nature of the relationship between personal motivation and scientific malpractice.